FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - JUAN NATHANAEL TEBIONO; IDA BAGUS NYOMAN SUKADANA (Jurnal Bisnis dan Akuntansi, 2019)
The purpose of this research is to examine the influence of firm size, return on asset, leverage, capital intensity ratio, sales growth, composition of the independent commissioner, and firm age to tax avoidance. The population of this research is all manufacture companies listed in Indonesia Stock Exchange from 2014-2016. The data source in this research was obtained from Indonesia Stock Exchange website. Samples are obtained through purposive sampling method, in which only 54 listed manufacture companies in Indonesia Stock Exchange meet the sampling criterias resulting 162 data available are taken as the samples. The research used multiple regression method to test the effect of each variable in influencing tax avoidance. The empirical result indicates that return on asset, and sales growth have influence to tax avoidance. However firm size, leverage, capital intensity ratio, composition of the independent commissioner, and firm age have no influence to tax avoidance.